The Influence of Capital Structure and Profitability on The Company Value of PT. Waskita Karya (Persero), TBK (Period 2016 To 2020) - Firdauz, Amelia; Ningsih, Tri; Sholihah, Sana (Acman: Accounting and Management Journal, 2024)
This study focuses on the specific time period of 2016-2020 and aims to ascertain and examine the impact of capital structure and profitability on the valuation of manufacturing companies listed on the Indonesia Stock Exchange. The independent variable X1 represents the capital structure, precisely measured by the debt-equity ratio (DER). The independent variable is the company PT. Waskita Karya (Persero), Tbk, a prominent manufacturing company, throughout the period of 2016-2020. The study population consisted of 12 years' worth of financial reports from PT Waskita Karya (Persero), Tbk, encompassing quarters 1-4. This totaled 48 financial reports. The sample for analysis was selected using the time series approach, resulting in 20 financial reports from 2016 to 2020. The data testing strategy employs several linear regression analysis methods, utilizing an alpha significance level of 5%. The findings of this study demonstrate that the capital structure has a notable adverse impact on the firm's value, reducing it by 22.4%. Conversely, profitability substantially positively influences the company's value, increasing it by 30.8%. Both capital structure and profitability have a 53.2% impact on firm value at the same time.